Carbon monoxide cycling in the Ria Formosa Lagoon (southern Portugal) during summer 2021 - Li, Guanlin; Ingeniero, Riel Carlo O (PANGAEA, 2023)
Discrete water samples for determining CO concentrations were collected using a Niskin bottle at approximately 1 m water depth from a small boat at 14 stations in the western part of the Ria Formosa Lagoon. Samples were taken in the late afternoon (~17:00h local time) on 25 May 2021. The sampling was repeated at approximately the same time on 26 May 2021. Additionally, atmospheric samples for CO were collected at Stations 8, 9, 10, 11, 12, and 14 on 26 May 2021. Incubation experiment using waters from the effluent of the aquaculture facility Estação Piloto de Piscicultura em Olhão (EPPO) at the Instituto Português do Mar e da Atmosfera, I. P. (IPMA, I. P.) in Olhão. Seawater was collected in 3.5 L UV-transparent incubation bottles and were placed into 200 L incubation enclosures (incubators) at CCMAR of the University of Algarve in Faro. Bottles were incubated under light and dark conditions to investigate photochemical CO production. A total of 16 bottles (separated equally) were distributed between two incubators. One incubator was set to light conditions (Group A), and the other was set to dark conditions (Group B). The experiments were carried out for 48 h, with sampling from the incubation bottles conducted at time points 0, 24, and 48 h. At each time point (14:00 h local time), triplicate samples were collected to determine dissolved CO concentrations and CDOM absorbance. Chlorophyll a (Chl-a), fluorescent dissolved organic matter (FDOM), salinity, pH, and water temperature (T) were measured on board in 0.5 m water depth using a calibrated EXO2 multiparameter sonde (YSI Inc. Yellow Springs, Ohio, USA).
Keywords: carbon monoxide; Ria Formosa Lagoon